Preparasi Katalis Cu/Silika Gel dari Kristobalit Alam Sabang serta Uji Aktivitasnya pada Reaksi Dehidrogenasi Etanol - Lubis, Surya (Jurnal Rekayasa Kimia & Lingkungan, 2009)
Cu/Silica gel catalyst preparation by using silica content which is obtained from Sabang natural crystobalit has been done. Isolated silica from crystobalit is reacted with natrium hidroxide to produce silicate natrium that reacted further with sulphate acid to produce silica gel. Silica gel is characterized by infra red spektroscopy dan BET test. BET test result showed that silica gel obtained has specific surface area 260,04 m2/gram and ion Cu impregnation into silica gel pores produce Cu/silica gel catalyst with spesific surace area 158,53 m/gram ith Cu2+ metal content = 193 ppm. Catalyst activation test Cu/silica gel at dehidrogenation reaction of etanol to produce asetaldehide was done at temperature 100oC 300oC. Reseach showed that the highest asetaldehide consentration (20,24%) is obtained at temperature 300oC. Keywords: asetaldehide, crystobalit, Cu/silica gel, dehidrogenation, ethanol